Association of Image-Guided Navigation With Complete Resection Rate in Patients With Locally Advanced Primary and Recurrent Rectal Cancer: A Nonrandomized Controlled Trial - Kok, Esther N. D. (JAMA Netw Open, 2020)
IMPORTANCE: The percentage of tumor-positive surgical resection margin rates in patients treated for locally advanced primary or recurrent rectal cancer is high. Image-guided navigation may improve complete resection rates. OBJECTIVE: To ascertain whether image-guided navigation during rectal cancer resection improves complete resection rates compared with surgical procedures without navigation. DESIGN, SETTING, AND PARTICIPANTS: This prospective single-center nonrandomized controlled trial was conducted at the Netherlands Cancer Institute—Antoni van Leeuwenhoek in Amsterdam, the Netherlands. The prospective or navigation cohort included adult patients with locally advanced primary or recurrent rectal cancer who underwent resection with image-guided navigation between February 1, 2016, and September 30, 2019, at the tertiary referral hospital. Clinical results of this cohort were compared with results of the historical cohort, which was composed of adult patients who received rectal cancer resection without image-guided navigation between January 1, 2009, and December 31, 2015. INTERVENTION: Rectal cancer resection with image-guided navigation. MAIN OUTCOMES AND MEASURES: The primary end point was the complete resection rate, measured by the amount of tumor-negative resection margin rates. Secondary outcomes were safety and usability of the system. Safety was evaluated by the number of navigation system–associated surgical adverse events. Usability was assessed from responses to a questionnaire completed by the participating surgeons after each procedure. RESULTS: In total, 33 patients with locally advanced or recurrent rectal cancer were included (23 men [69.7%]; median [interquartile range] age at start of treatment, 61 [55.0-69.0] years). With image-guided navigation, a radical resection (R0) was achieved in 13 of 14 patients (92.9%; 95% CI, 66.1%-99.8%) after primary resection of locally advanced tumors and in 15 of 19 patients (78.9%; 95% CI, 54.4%-94.0%) after resection of recurrent rectal cancer. No navigation system–associated complications occurred before or during surgical procedures. In the historical cohort, 142 patients who underwent resection without image-guided navigation were included (95 men [66.9%]; median [interquartile range] age at start of treatment, 64 [55.0-70.0] years). In these patients, an R0 resection was accomplished in 85 of 101 patients (84.2%) with locally advanced rectal cancer and in 20 of 41 patients (48.8%) with recurrent rectal cancer. A significant difference was found between the navigation and historical cohorts after recurrent rectal cancer resection (21.1% vs 51.2%; P = .047). For locally advanced primary tumor resection, the difference was not significant (7.1% vs 15.8%; P = .69). Surgeons stated in completed questionnaires that the navigation system improved decisiveness and helped with tumor localization. CONCLUSIONS AND RELEVANCE: Findings of this study suggest that image-guided navigation used during rectal cancer resection is safe and intuitive and may improve tumor-free resection margin rates in recurrent rectal cancer. TRIAL REGISTRATION: Netherlands Trial Register Identifier: NTR7184